2020
DOI: 10.3389/fpsyg.2020.561590
|View full text |Cite
|
Sign up to set email alerts
|

Acute Aerobic Exercise Ameliorates Cravings and Inhibitory Control in Heroin Addicts: Evidence From Event-Related Potentials and Frequency Bands

Abstract: Objective: Aerobic exercise is considered a potential adjunctive treatment for heroin addicts, but little is known about its mechanisms. Less severe cravings and greater inhibitory control have been associated with reduced substance use. The aim of the current study was to determine the effects, as measured by behavioral and neuroelectric measurements, of acute aerobic exercise on heroin cravings and inhibitory control induced by heroin-related conditions among heroin addicts. Design: The present study used a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 67 publications
(92 reference statements)
0
9
0
Order By: Relevance
“…In clinical studies, different types of exercise have been used to treat human cognitive disorders and substance abuse disorders, including yoga, weightlifting, running on a treadmill, swimming, indoor cycling, and use of a stationary bicycle, all of these on a voluntary basis ( (Wang et al, 2020); for reviews, see Barha et al, 2017;Hallgren et al, 2016;Weinstock et al, 2017). One study focused on high-intensity aerobic exercise using a treadmill, a stationary bicycle, or an elliptical machine (75%-85% heart rate during exercise sessions), and how it improved cognitive functions in women diagnosed with amnestic mild cognitive impairment (MCI), a transitional stage of cognitive function between normal aging and dementias defined by Baker et al (2010) and Cui et al (2018).…”
Section: T Ype S Of E Xercis E Us Ed In Clini C Al and Preclini C Al ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical studies, different types of exercise have been used to treat human cognitive disorders and substance abuse disorders, including yoga, weightlifting, running on a treadmill, swimming, indoor cycling, and use of a stationary bicycle, all of these on a voluntary basis ( (Wang et al, 2020); for reviews, see Barha et al, 2017;Hallgren et al, 2016;Weinstock et al, 2017). One study focused on high-intensity aerobic exercise using a treadmill, a stationary bicycle, or an elliptical machine (75%-85% heart rate during exercise sessions), and how it improved cognitive functions in women diagnosed with amnestic mild cognitive impairment (MCI), a transitional stage of cognitive function between normal aging and dementias defined by Baker et al (2010) and Cui et al (2018).…”
Section: T Ype S Of E Xercis E Us Ed In Clini C Al and Preclini C Al ...mentioning
confidence: 99%
“…Diverse types of exercise, such as use of a stationary bicycle, walking, yoga, and jogging, are being used to study the effect of exercise on heroin consumption and withdrawal symptoms (Table 4). A clinical study showed that heroin‐dependent male participants who engaged a single time in stationary bicycle exercise had an immediate effect on attenuating heroin cravings, that lasted for about 40 min after aerobic exercise treatment (Wang et al., 2020). According to self‐reports from people diagnosed with OUD, those involved in aerobic exercise treatment programs which involved walking or cycling showed an attenuation of opioid consumption (Neale et al., 2012).…”
Section: Effects Of Exercise On Substance Use Disordersmentioning
confidence: 99%
“…This protocol was designed to train the cortex associated area, particularly the anterior cingulate gyrus associated area (i.e., Fz and Cz) which found to be vital for the higher-ordering cognitive functions (Wang et al, 2020). This protocol was implemented on Fz to improve the inhibitory behaviours and executive functioning as well as Cz to improve motor functions of K. Meanwhile, the design of this particular training protocol was mainly based on the preintervention QEEG brain mapping assessment as displayed in Figure 3.1, which indicated the dominance of the slow bandwidth brainwaves (i.e., delta and alpha brainwaves).…”
Section: Rewarding Smr On Fz and Czmentioning
confidence: 99%
“…Those with SUD experience a significant health burden, including a higher prevalence of diabetes, cardiovascular disease, cancer, infectious diseases, decreased quality of life, and high levels of co-occurring mental disorders [2][3][4]. Poly-SUDs (i.e., dependence on two or more substances) are highly prevalent and associated with greater psychopathology, poorer treatment outcomes, and higher rates of fatal overdoses than individual SUDs [5,6]. Treatments include psychological/behavioral therapy and medication typically administered during hospitalization.…”
Section: Introductionmentioning
confidence: 99%